Investigating the association between tobacco use and oral health among security guards at a tertiary healthcare centre in New Delhi: a cross-sectional study - Neha Chauhan; Sarah Paul; Upendra Singh Bhadauria; Bharathi M. Purohit; Ritu Duggal; Manali Deb Barma; Deepali Agarwal; Anuradha Bhukal; S Sasidharan; Pallavi Shukla; Maroof Khan; Ramya Shenoy; et al. (Frontiers Media S.A., 2024)
BackgroundTobacco usage is a major global public health concern, contributing to millions of deaths annually. This study focuses on security guards, an occupational group facing unique challenges, to investigate tobacco prevalence, usage patterns, and associated oral health risks.MethodsA cross-sectional study was conducted among security guards at a Tertiary Health Care Centre, from October 2022 to February 2023. Data on demographics, tobacco habits, and comorbidities were collected via a structured questionnaire. Clinical oral examinations provisionally diagnosed Oral Potentially Malignant Disorders (OPMDs) based on clinical findings. Appropriate Statistical analyses were employed.ResultsAmong 696 security guards, 40.1% used tobacco, including 15.0% smokers and 74.5% engaging in smokeless tobacco. Additionally, 10.3% reported using both smoking and smokeless forms. Non-tobacco users accounted for 59.9%. Tobacco users showed a higher prevalence of OPMDs (11.4%) compared to non-tobacco users (1.4%).DiscussionSecurity guards demonstrated a higher tobacco prevalence, with smokeless tobacco being predominant. Gender disparities in tobacco use emphasize the need for gender-specific interventions. The study highlights the significant impact of tobacco on oral health, especially the risk of OPMDs.ConclusionA high prevalence of tobacco usage (40.1%), particularly smokeless tobacco, among security guards, emphasizes the importance of targeted interventions within this occupational group. Oral Potentially Malignant Disorders (OPMDs) were significantly more prevalent (11.4%) in tobacco users. The association between tobacco usage and OPMDs reaffirms the well-established association between tobacco and adverse oral health outcomes.